(untitled) (INNOVATIVE ECONOMY, 2025)
Trostianska K.M. TRANSFORMATION OF BUSINESS MODELS UNDER THE IMPACT OF DIGITALIZATION: GLOBAL TRENDS AND THE UKRAINIAN CONTEXT Purpose. The aim of the article is to identify and substantiate the impact of digitalization processes on the transformation of business models in the global and national contexts, taking into account the institutional, resource, behavioural, and system-network dimensions of the entrepreneurial environment. Methodology of research. A complex of complementary methods was used in the work. The comparison method was used to analyse global and national trends in digital trade and IT services. The systematization method made it possible to structure the results within the Business Model Canvas framework, reflecting the impact of digitalization on the key blocks of a business model. The critical analysis of literature and analytical reports (UNCTAD, WTO, NBU, State Statistics Service of Ukraine, Statista) was employed to summarize the evidence base. The generalization method was applied to formulate conclusions and directions for further research. Findings. It is substantiated that digitalization acts as a systemic factor in the transformation of business models, influencing all components of the Business Model Canvas. It is established that in the global context, the key drivers are the growing share of e-commerce and digitally delivered services in the structure of world exports. For Ukraine, a dual effect of digitalization is identified: on the one hand, war-related risks (logistics disruption, resource constraints) slow down its pace; on the other hand, the role of digital channels in maintaining connections with clients and partners is increasing. It is also determined that digital trade stimulates the transition of enterprises to new formats of business models: direct-to-consumer (D2C), multi-sided platforms (B2B2C), and personalized service-oriented models. Originality. An integrative approach to analysing the impact of digitalization on business models has been developed, which, unlike existing approaches, combines the Business Model Canvas with the multidimensional framework of the entrepreneurial environment (institutional, resource, behavioural, and system-network dimensions). This makes it possible not only to describe the individual effects of digitalization but also to explain the mechanisms of business model transformation under different conditions, including the wartime context. Practical value. The proposed results can be applied by enterprises in retail trade, IT services, logistics, and e-commerce to improve business models in line with digital trends. Their implementation will ensure the expansion of sales channels, strengthening of partnerships, and enhancement of flexibility and competitiveness in the global digital economy. Key words: digitalization, business model, e-commerce, digital services, Business Model Canvas, entrepreneurial environment, innovative business models, business process analytics, forecast, digital transformation analysis.